Asafici – śpiewacy świątynni doby powygnaniowej - Stabryła, Wojciech Maciej (Studia Pastoralne, 2026)
The paper addresses the group of temple singers, collectively known as Asaphites. They derived from the Northern Kingdom, but, after its fall in 721 B.C., they moved to the Southern Kingdom where they joined the temple service in Jerusalem. After the temple destruction in 586 B.C., they were resettled to Babylon where they continued their activity. After returning from the exile to Jerusalem, they became actively involved in restoring cult at the temple. The first part of the paper describes the features confirming the homogeneity of the Psalms of Asaph (Ps 50 and 70-83), while the next part focuses on the School of Asaph and the last one on Asaphites as guardians of tradition.